Flagellin and outer surface proteins from Borrelia burgdorferi are not glycosylated - Štěrba, Ján (Jihočeská univerzita, 2012)
Glycosylation of four proteins from Borrelia burgdorferi s.s. was investigated ? flagellins FlaA, FlaB, and outer surface proteins OspA and OspB. Glycosylation of these four proteins was not proved by any of the used techniques. However, other glycan-staining positive proteins were present in the borrelia samples. These proteins were suggested to originate in the culture medium.
Flagellin and outer surface proteins from Borrelia burgdorferi are not glycosylated
Keywords: Lyme disease; Borrelia burgdorferi; glycosylation; flagellin; Osp; Lyme disease; Borrelia burgdorferi; glycosylation; flagellin; Osp